Shared neural correlates of limb apraxia in early stages of Alzheimer's dementia and behavioural variant frontotemporal dementia. (November 2016) - Johnen, Andreas; Brandstetter, Lisa; Kärgel, Christian; Wiendl, Heinz; Lohmann, Hubertus; Duning, Thomas
Abstract: Limb apraxia denotes a cognitive impairment of gesture production. Lesion studies in patients with stroke point towards distinct neural processing streams for limb imitation and object-pantomime within left parietal and temporal cortex, respectively. Despite its frequent occurrence as an early symptom in both, Alzheimer's dementia (AD) and behavioural variant frontotemporal dementia (bvFTD), neural correlates of limb apraxia within these patient groups remain unexplored. Using voxel-based morphometry and multiple regression models, associations between limb apraxia and gray matter (GM) volume were investigated in 36 dementia patients (18 AD, 18 bvFTD) in early disease stages. Both dementia subtypes showed a comparable degree of limb apraxia. Although the patient groups showed distinct atrophy patterns with significantly more severe frontal GM loss in bvFTD, we found similar neural correlates of limb apraxia within posterior brain regions for both dementia subtypes: limb-imitation was associated with bilateral atrophy of superior, inferior and medial parietal cortex. Object-pantomime showed associations with GM volume in right middle temporal and angular gyrus. Our results argue for shared neural correlates of limb apraxia in AD and bvFTD and validate the syndrome as an important neuropsychological feature across different etiologies. Moreover, our results are compatible with neural models derived from patients with stroke, suggesting partly distinct neural representations of imitation and pantomime. Compared to patients with stroke however, AD and bvFTD showed more bilateral or even right lateralized neural representations of limb apraxia, proposing a greater influence of visuospatial impairments and spatial body representation deficits on praxis performance.